Application of ultrafiltration in the study of phenolic isolates and melanoidins from pale and black brewers' spent grain. (17th March 2014) - Piggott, Charles O.; Connolly, Alan; FitzGerald, Richard J.
Summary Two types of brewers' spent grain (BSG), pale and black, were studied employing ultrafiltration (UF cut‐off, 10 kDa) to obtain high‐molecular‐weight (HMW) and low‐molecular‐weight (LMW) phenolic fractions from one pale (P2) and one black (B2) BSG extracts. Of the four UF fractions obtained, the HMW B2 fraction had highest level of polyphenols (5.73 ± 0.25 mg GAE g−1 BSG dw) and protein (18.82 ± 0.41 mg protein g−1 BSG dw). Metal‐chelating ability and antioxidative properties were also identified. Antioxidant activity evaluated using the DPPH and FRAP assays, indicated that activity in B2 extracts was associated mainly with the HMW fraction (3.10 ± 0.10 and 2.49 ± 0.09 TE g−1 BSG dw, respectively), whereas in P2 samples, antioxidant activity was highest in LMW fractions (0.58 ± 0.01 and 0.92 ± 0.03 TE g−1 BSG dw, respectively). The high antioxidant activity and metal‐chelating ability observed for black BSG extracts may be attributed to the presence of coloured melanoidinic structures.